Healing the Soul, Connecting the Social: Spirit-Based Practices in Modern Religious Life - Anila Hassan; Dr. Saira Batool (Journal of Religion and Society, 2025)
This study explores the goals and methods of healing practices and therapeutic encounters guided by a Sufi Saint and their influence on visitors at Dua House. The research includes perspectives from both the spiritual guide and the seekers, offering a broader view. While previous studies have focused on medical and psychological aspects, this study emphasizes the social and spiritual factors affecting healing experiences. Using constructivist grounded theory, 13 semi-structured interviews were purposively sampled and analyzed. The analysis generated categories offering theoretical insights into the healing process. Results indicate that the pursuit of spiritual healing can stem from both challenging life circumstances and an innate desire for a divine connection. Spiritual practices aim to purify the human soul. Through continuous remembrance of Allah, the aura of spiritual places and the teachings of Sufi Saints are believed to have a profound transformative effect. These practices promote moral correction, strengthen faith, and foster social inclusion, as well as psychological and physical well-being. The study emphasizes the importance of a spiritual guide and proposes key criteria for identifying an authentic Sufi Saint. Overall, the findings demonstrate the positive impact of spiritual healing on individuals and highlight its broader sociological significance, offering new insights into the sociology of religion. Keywords: Spiritual Healing, Divine Intervention, Sufi Saint, Therapeutic Encounters, Sociology of Religion, Grounded Theory. https://doi.org/10.5281/zenodo.17259354